STRATEGI PENGEMBANGAN KUALITAS PELAYANAN PUBLIK DI KECAMATAN SUMEDANG UTARA PADA MASA PANDEMI COVID-19 - Fepi Febianti; Kristina Apriani; Muhammad Ridza Syafardan; Puteri Indah Islamiati; Risa Nur Faujiah; Wulan Sari Budiani (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2021)
This study aims to determine, get the data data and objective information abaout Strategy for the Development of Public Service Quality in Kecamatan Sumedang Utara during the Covid-19 Pandemic. In this study, using qualitative research methods with data collection, observation steps, in-depth interviews and documentation. From this research, the results obtained are the factors that support the Quality of Public Services in the Strategy for the Development of Public Service Quality in Kecamatan Sumedang Utara during the Covid-19 Pandemic as a whole. using technology, lack of ability or skills resulting in mismatches in dealing with competency problems. Obstacles were encountered regarding the Quality of Public Services in the Strategy for Developing the Quality of Public Services in Kecamatan Sumedang Utara during the Covid-19 Pandemic, namely: in terms of budget, interest or awareness of employees, facilities, and when employees face new things, lack of funds and environmental conditions or organizational climate that is not supportive, lack of expertise in the analysis phase of a problem at hand, does not meet predetermined standards, mistakes occur if you collect data too quickly. Efforts to overcome obstacles include developing potential, training and developing continuously, using analytical techniques in problem solving, anticipating complex problems, working beyond / meeting standards, work carried out accurately according to the competence of employees in the Service Sector in North Sumedang District.